Reconceptualizing the Validity of Cross-Paradigm Research through a Critical Review of Reliability, Credibility, and Trustworthiness - Mohamad Yunus Laia; Rahmah Fithriani; Amirul Mukminin; Saiful Anwar Matondang (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
The This study aims to reconceptualize the validity of cross-paradigm research through a critical examination of the evolution of the meaning and function of reliability, credibility, and trustworthiness in the methodological literature. This study departs from the problem of conceptual fragmentation and epistemological tension that arise due to the application of validity criteria ahistorically and procedurally in various research paradigms. The method used is a non-systematic literature review of conceptually relevant Scopus indexed journal articles, with a thematic-conceptual analysis approach and cross-paradigm critical synthesis. The results of the study show that validity has shifted from technical-instrumental attributes to epistemic justification processes that are contextual, reflective, and paradigmatic. Reliability no longer serves as a universal prerequisite for validity, but rather as a technical mechanism whose relevance depends on certain epistemological assumptions. Credibility develops as an interpretive justification mechanism in qualitative research, while trustworthiness serves as a reflective evaluative framework that emphasizes transparency and accountability. This study also found epistemological tensions, conceptual inconsistencies, and theoretical limitations in the use of these three concepts across paradigms. In conclusion, the validity of research needs to be understood as a dynamic practice of epistemic justification and not reduced to a methodological checklist. This research contributes to the development of research methodology by offering a conceptual synthesis that goes beyond the classical dichotomy of validity–reliability and trustworthiness–credibility.